THE PURPOSE OF EMPLOYING GAMES IN TEACHING LANGUAGES TO SECONDARY STUDENTS - Raxmonov Timur Ag’zam o’g’li (Western European Studies, 2025)
This paper explores the effectiveness and educational value of using games as a pedagogical tool in language instruction for secondary school students. As traditional teaching methods may not fully engage or motivate learners, game-based learning offers an interactive and studentcentered alternative that fosters participation, communication, and collaboration. The integration of games in language education can enhance vocabulary acquisition, grammar comprehension, and speaking and listening skills, all while creating a low-stress environment that encourages experimentation and reduces anxiety. This study examines various types of games—digital, board-based, and role-playing—and their specific contributions to language development.
Keywords: Games; secondary education; second language; scientists